Somal and axonal translation in Parkinson's dopamine neurons: Sequencing the translatome - Kilfeather, P (2021)
Nigrostriatal dopamine neurons have long, highly arborised axons, indicating a requirement for axonal translation. The axonal ‘translatome’ will reflect the neuronal response to local stressors that precedes cell death in Parkinson’s disease (PD) as well as revealing key transcriptional differences between protected and vulnerable dopaminergic populations. The translating ribosome affinity purification (TRAP) technique enables the capture of translating ribosomes specifically in dopaminergic neurons by expressing an enhanced green fluorescence protein (eGFP)-tagged ribosomal subunit driven by a cell type-specific promoter.